2010
DOI: 10.1093/ndt/gfq398
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of renal replacement therapy (RRT) in the diabetic compared with the non-diabetic population in a German region, 2002-08

Abstract: In this population-based study in a German region, we found the relative risk of RRT in the estimated adult diabetic population to be 8-fold increased compared with the non-diabetic population. A high proportion of the RRT risk can be attributed to diabetes in the diabetic as well as in the whole population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
0
22
0
3
Order By: Relevance
“…Male sex increases the incidence, prevalence and progression of chronic kidney disease [9]. Thus, most of the patients that need renal replacement therapy are men [10]. Although these phenomena have always been attributed to the protective effects of estrogens, recently it has been suggested that male hormones may play a critical role in these differences [11].…”
Section: Introductionmentioning
confidence: 99%
“…Male sex increases the incidence, prevalence and progression of chronic kidney disease [9]. Thus, most of the patients that need renal replacement therapy are men [10]. Although these phenomena have always been attributed to the protective effects of estrogens, recently it has been suggested that male hormones may play a critical role in these differences [11].…”
Section: Introductionmentioning
confidence: 99%
“…DM2 interacts with other major risk factors such as hypertension and dyslipidemia, increasing the risk for micro- and macrovascular morbidity such as chronic kidney disease (CKD), end-stage renal disease (ESRD), atherosclerosis, coronary heart disease and cerebral ischemia [2-5]. For example, diabetic nephropathy is the underlying kidney disease of about every third patient starting renal replacement therapy [6-11]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have tended to report incidence of RRT in diabetes as opposed to prevalence. 12 , 13 A large European study comprising of 10 registries showed a small increase in the incidence of RRT for T1DM and a marked increase in the incidence of RRT in T2DM between 1991 to 2000(4). UK registry data showed 15.2% of prevalent patients had diabetes as their PRD and 25% of new incident patients.…”
Section: Resultsmentioning
confidence: 99%